High-performance [EMIM][Tf₂N]-grafted silica/polysulfone hybrid membranes for enhanced CO₂/CH₄ separation: An experimental and computational approach - Mehtab Ali, Darban; Serene Lock, Sow Mun; Waqar, Hussain; Sharjeel, Waqas; Lim, Lam Ghai; Irene Lock, Sow Mei; Kang, Dun-Yen; Mohd Hafiz Dzarfan, Othman; Ban, Zhen Hong; Yiin, Chung Loong; Suhaib Umer, Ilyas; Cheng, Loh Jia (Elsevier B.V., 2026)
Background Mixed matrix membranes (MMMs) containing three components consisting of a polymeric continuous phase, a solid inorganic material, and an ionic liquid are widely explored for CO₂ removal from natural gas to increase energy content, reduce corrosion, and enable safer utilization. However, most of the previous studies have relied on physically blended or impregnated ionic liquids (ILs), which suffer from leaching and membrane instability, ultimately limiting their separation performance. Moreover, experimental methods alone cannot fully explain gas transport mechanisms or interactions between polymers, fillers, and gases with sorption sites. Methods This work employs a grafting strategy to covalently support 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([EMIM][Tf₂N]) onto silica surface (IL-Si), ensuring long-term stability, uniform dispersion, improved compatibility between polymer and filler, and enhanced gas separation performance. Hybrid membranes with filler contents ranging from 5 to 20 wt.% were experimentally fabricated and analysed from an atomistic perspective using molecular dynamics (MD) simulations. Significant Findings The IL-functionalized filler enhanced interfacial adhesion, as evidenced by increased thermal stability with delayed degradation and improved glass transition temperature (Tg) from 181.5 to 189.46 °C, reflecting stronger polymer-filler interactions. At 10 wt.% IL-Si, the membrane achieved a CO₂ permeability of 25 Barrer and CO₂/CH₄ selectivity of 37, representing 246% and 208% improvements over neat polysulfone (PSF). Compared to non-modified silica/PSF, the permeability and selectivity improved by 140% and 40%, respectively. MD simulations, with <10% deviation, confirmed [Tf₂N]⁻ anions enhance CO₂ sorption while [EMIM]⁺ cations strengthen filler dispersion and compatibility. Based on this, future work needs to focus on testing functionalized ILs, scaling up fabrication, assessing long-term stability under harsh conditions, and expanding membrane studies to other relevant gas pairs.